2018
DOI: 10.1093/heapro/day082
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to components of Health Promoting Schools in schools of Bengaluru, India

Abstract: Schools provide a crucial platform for health promotion as the school years are a vital stage in one’s life, where lifelong general and oral health-related behaviours are developed and established. The components of Health Promoting Schools (HPSs) suggested by World Health Organization provide guidance for facilitating health promotion within this setting. This study aimed to assess the adherence to the components of HPSs amongst schools in Bengaluru, India utilizing a comprehensive tool developed for the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…11 Periyasamy found that 72.1% of the schools were situated well away from the busy roads and Kofoworade found that 13.3% were in industrial areas. 12,13 The problem of air/noise pollution among schools observed in this study may be because of their location in the congested and/or industrial town. The site of schools should be on suitable high land.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…11 Periyasamy found that 72.1% of the schools were situated well away from the busy roads and Kofoworade found that 13.3% were in industrial areas. 12,13 The problem of air/noise pollution among schools observed in this study may be because of their location in the congested and/or industrial town. The site of schools should be on suitable high land.…”
Section: Discussionmentioning
confidence: 86%
“…A similar pattern was observed by Periyasamy (72.1% private and 27.9% government schools). 12 But according to Jiya, the proportion of public schools (73.6%) was more than private schools (26.4%) in their study area. 16 In our study, 13 (68.4%) government schools were in the rural area while six (31.6%) were in the urban area.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations